(untitled) - Shida, Tadamasa (New York, 2004)
Providing the quantum-mechanical foundations of chemical bonding, this unique textbook emphasizes key concepts such as superposition, degeneracy of states and the role of the electron spin. These quantum mechanical notions are usually oversimplified or meticulously circumvented on other books, to the frustration of serious readers who want to understand, for example, why two protons can be stably bound with only one electron to make the simplest molecule H2+. An initial, concise and compact presentation of the rudiments of quantum mechanics enables readers to progress through the back with a firm grounding. Experimental examples are included to illustrate how the abstract concepts are manifest in real systems.
Keywords: Chemical bonds